Enhancing Conceptual Understanding in Islamic Education Through a Hypercontent Digital Flipbook in Blended Learning: Evidence from Indonesian Madrasah - Miftah Hur Rahman Zh; Cynthia Mayang Sari; Zahid Zufar At Thaariq; Ilham Sumalee; Athia Nur Kamilah (Jambi Tuah Tengganai, 2026)
Conceptual understanding in Quranic studies requires learners to integrate Arabic text, recitation, exegesis, historical context, and contemporary application, an inherently multilayered and nonlinearly structured knowledge domain that linear print materials struggle to support. This study developed and evaluated a hypercontent digital flipbook within a blended learning structure to enhance conceptual understanding in Qur'anic studies at an Indonesian madrasa. Recognizing that linear print materials inadequately reflect the multilayered, nonlinear nature of religious knowledge, we designed a web-based flipbook that integrates Arabic text, translation, concise tafsir, audio recitation, animated explanations, and gamified assessment. Following the ADDIE model, we validated the artifact across four expert domains (instrument, learning strategy, media, content), conducted a small-group usability trial (n=20), and implemented a single-group pretest-posttest design with 36 Grade XI students from a state Islamic senior high school in East Java. Expert validation yielded ratings between 78% and 98.5%, while student acceptance ranged from 91% to 90.56% across trials. Pretest mean scores of 68.33 (61.11% mastery) increased to 81.09 (91.67% mastery) at posttest, with paired-samples t(35) = 22.23, p < .001, mean increase = 11.94 points, and Cohen's dz = 3.70. Hake's normalized gain of 0.38 indicated moderate educational improvement. However, the pre-experimental design, identical pretest-posttest items, and single-site sample preclude causal attribution. We articulate a candidate mechanism whereby nonlinear navigation supports conceptual integration across content layers. Future research requires quasi-experimental dismantling designs, multi-site replication, and delayed retention measures.